An innovation of character of Islamic religious studies education towards education 4.0 in Elementary School: Bibliometric Reviews - Elihami Elihami (Jurnal Basicedu, 2022)
This research explained an innovation of Islamic religious studies education towards education 4.0 in Elementary School through bibliometric review from 2010-2021. The VOS viewer application is used to analyze the retrieved bibliographic review. The performance of the most productive authors, journals, keywords, and citation references is examined. The rate of relative growth and the time required to double had been calculated in 2010-2021. The study results found how to act so that educators of guidance and advice with Islamic religious education teachers are responsible for developing moral character. The two play an important part which can be achieved when working together. The novelty and contribution of the research are the studies carried out can be seen that an innovation of character of Islamic religious studies education towards education 4.0 in Elementary School.